Terciptanya Indonesia Emas 2045: Melalui Evolusi Budaya Politik Indonesia Yang Berkesadaran Hukum Oleh Pemuda dan Penggunaan Solusi Digital - Farhan, Farhan Azmy Rahmadsyah (Taruna Law: Journal of Law and Syariah, 2025)
Indonesia is experiencing turbulent political waves, striving towards change, building pillars of evolution with legal awareness. If we look at Indonesia's current political dynamics, there is extensive use of practical politics without involving law and ethics in its implementation, for example, thuggery in politics, identity politics that damages national unity, and the practice of money politics. Indonesia is a constitutional state according to Article 1, Paragraph 3 of the 1945 Constitution. Therefore, all decisions taken should be based on law, including all political decisions. Although in reality, there are still many violations in the implementation of politics in Indonesia. The research used in this article is a qualitative research method. When discussing political theory, there are several theories considered important, namely: liberal, conservative, and socialist theories. Indonesia does not adhere to one dominant political system; in other words, Indonesia incorporates everything considered good and appropriate in its state implementation. Thus, the author provides ideas and solutions including: building a transparent and accountable digital political ecosystem, implementing artificial intelligence (AI) in political monitoring and analysis, developing an inclusive digital political education system, building an active and collaborative digital political community. These ideas and solutions focus on utilizing digital technology, artificial intelligence, and political education, especially early political education for youth, to become a cornerstone of quality political change for Indonesia in the future (changing legal culture through generational truncation efforts).